The Role of Environmental Principles in Mining Resources: A Discourse of Islamic and Indonesian National Law - Hidayah, Ahdiyatul; Fahrozi, Faturrahman; Rifani, Ahmad (Faculty of Law, Jambi University, 2023)
Human life is inherently intertwined with the environment, serving as the backdrop for all daily activities. It is within this environment that individuals fulfill basic needs such as sustenance, shelter, and resources, often without a full appreciation of the environment's profound significance. The extraction and utilization of resources, particularly from mines within the Earth, play a pivotal role in meeting human needs. This study highlighted that mine, as products derived from the Earth's depths, merit responsible stewardship to ensure sustainable use. It is imperative for humans to recognize the broader societal implications of mining activities beyond personal interests. Islamic principles advocate for the equitable distribution of mining resources as a communal right and shared property. This perspective allows for the enjoyment of these resources by all individuals. Islam does not preclude the delegation of mining resource management to the government, emphasizing national prosperity. In tandem with Islamic principles, Positive Law acknowledges the government's authority to grant mining rights to various entities. Private businesses, cooperative entities, and individuals are among those eligible for such rights, contingent upon obtaining proper business licenses from relevant authorities. This legal framework aligns with the overarching goal of fostering national development and ensuring responsible resource management for the benefit of society.